2021
DOI: 10.1002/ange.202113420
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights of Irreversible Li+ Intercalation in MnO2 Electrode

Abstract: Tunnel-structured MnO 2 represents open-framed electrode materials for reversible energy storage. Its wide application is limited by its poor cycling stability, whose structural origin is unclear. We tracked the structure evolution of b-MnO 2 upon Li + ion insertion/extraction by combining advanced in situ diagnostic tools at both electrode level (synchrotron X-ray scattering) and single-particle level (transmission electron microscopy). The instability is found to originate from a partially reversible phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…By summarizing and analyzing, it can be concluded that the intercalation of charged metal ions affects the electronic structure of manganese-based materials, regardless of the crystal configuration with different spacing between the layers or channels with different sizes. The changes in the electronic structure are mainly concentrated on the oxidation state of Mn ion, atomic coordination environment, charge density distribution, and distribution of different atomic electron orbitals, 137 which are clearly confirmed by XPS, 138 EELS, 139 XAS 122 characterization results, and the DFT calculation results including differential charge analysis, Bader charge analysis, ELF, 132 DOS, and PDOS. 140 Finally, electronic structure regulation realizes the optimization of electrochemical performance, mainly reflected in the acceleration of guest ion transport in the host structure, 141 the improvement of electronic conductivity and ionic conductivity, 135 the strengthening of stability, and many other aspects, which is conducive to the practical application of manganese-based materials as the cathode in ZIBs.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 61%
See 1 more Smart Citation
“…By summarizing and analyzing, it can be concluded that the intercalation of charged metal ions affects the electronic structure of manganese-based materials, regardless of the crystal configuration with different spacing between the layers or channels with different sizes. The changes in the electronic structure are mainly concentrated on the oxidation state of Mn ion, atomic coordination environment, charge density distribution, and distribution of different atomic electron orbitals, 137 which are clearly confirmed by XPS, 138 EELS, 139 XAS 122 characterization results, and the DFT calculation results including differential charge analysis, Bader charge analysis, ELF, 132 DOS, and PDOS. 140 Finally, electronic structure regulation realizes the optimization of electrochemical performance, mainly reflected in the acceleration of guest ion transport in the host structure, 141 the improvement of electronic conductivity and ionic conductivity, 135 the strengthening of stability, and many other aspects, which is conducive to the practical application of manganese-based materials as the cathode in ZIBs.…”
Section: Energy and Environmental Science Reviewmentioning
confidence: 61%
“…It is notable that different guest ions have different regulatory effects, and the suitable types of intercalated ions are expected to effectively optimize the electrochemical properties of manganese-based materials. The researched intercalated metal ions include univalent (Li + , 121 Na + , 122,123 K + 124–126 ), bivalent (Zn 2+ , 127 Cu 2+ , 128,129 Mg 2+ , 130 Ca 2+ , 131 Ce 2+ , 69 Co 2+ 132 ), and polyvalent ions (Al 3+ , 133 La 3+ , 7,134 V 5+ 135 ).…”
Section: Regulation Strategies For Electronic Structuresmentioning
confidence: 99%
“…The intense peak means that the 3@LRMO sample maintains the crystallinity well, indicating that only a small disordered amorphous region is generated during the (de)lithiation processes. [54][55][56] The phase transformation consists of three stages: layered structure, disordered structure, and spinel phase. 57 Therefore, the less disordered region in the 3@LRMO electrode indicates that the transformation from the layered structure into the spinel structure is effectively suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…The difference is that the diffraction peak intensity of the 3@LRMO electrode is higher than that of the LRMO electrode, especially at the second charge end (Figure 5). The intense peak means that the 3@LRMO sample maintains the crystallinity well, indicating that only a small disordered amorphous region is generated during the (de)lithiation processes 54–56 . The phase transformation consists of three stages: layered structure, disordered structure, and spinel phase 57 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although constructed by the same [MnO 6 ] units, the polymorphic OMS exhibit distinct ion transport properties [67,68] . For example, while α‐MnO 2 (2×2 tunnels) transports Li + following an anisotropic pattern, such kinetic features are not seen in β‐MnO 2 (1×1 tunnels), [69] or t‐MnO 2 (3×3/3×4 tunnels) [46] . Instead, β‐MnO 2 shows partially reversible lattice evolution upon (de)lithiation, during which phase separation occurs and accounts for the partial irreversibility [69] …”
Section: Ion Transport Kinetics Within Oms Tunnelsmentioning
confidence: 99%